Effect of supplemental pig milk replacer on piglet weight gain and sow backfat thickness - Győri, Zsolt; Balogh, Péter; Huzsvai, László; Novotniné Dankó, Gabriella (Acta Agraria Debreceniensis, 2015)
Sow milk production is the major factor limiting pig growth to weaning. Although the milk production of the sows incremental many environmental factors affect the actual performances. The supplemental milk replacer can be an appropriate solution to ward off disparities and try to equalize the available milk quantity to the piglets according to their appetite, to enlarge the weight of pigs at weaning, ultimately. The aim of the present study was to investigate the effects of liquid milk supplement on weight development and litter performance of the piglets during the suckling period. Data were collected from 60 farrowings, the weight of 649 piglets in a total were measured at birth, 14 days old and at weaning (28 days), respectively. In the control group (n=319) the piglets were suckled and got prestarter feed from day 10. In the experimental group (n= 330) the piglets had got liquid milk replacer in 10.71% solution, from day 10 after birth together with suckling and prestarter feed, as well. Based on the Duncan's multiple range tests, there were no significant differences in birth weight between the control and experimental group but we found significant differences between the 14 days weight and the weaning weight, subsequently. Based on the CV% of weight the experimental group became more homogenous, in contrary to the weight of the control group at the end of suckling period. The milk supplementation can be an appropriate solution to ward off disparities and to equalize the available milk quantity to the piglets according to their appetite, to enlarge and uniform the weight of pigs at weaning, ultimately.